TREND OF THE MODERN TIMES: MEDICALIZATION OF CULTURE - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the problem of social constructing of the norms and pathologies in the sphere of ideas of the health in the modern society.